Coaching Pembuatan Website Commerce Untuk UMKM di Wilayah Sukapura Kiaracondong Bandung - Sarifiyono, Aggi Panigoro; Hadiantini, Ratih (LPPM UNIBI, 2023)
Technological Development and Business Change: Digital transformation has changed the business paradigm globally. The use of the internet and adoption of technology has become the key to expanding market reach and increasing competitiveness. However, many MSMEs have not utilized the full potential of this technology due to a lack of knowledge and skills in the digital field. Local MSME Potential Sukapura and Kiaracondong Districts have many MSMEs with unique products and large market potential. However, many of them do not yet have a strong online presence to market their products widely. In general, by designing a website, utilizing the marketplace, and being active on social media, Rinkadaily can optimize marketing strategies to increase its online presence and business growth in the fashion and knitted sweater industry. The website acts as an efficient information center, the marketplace helps in expanding and increasing sales, while social media functions as a tool for interaction with customers and promotion of services. The integration of digital marketing strategies, including paid advertising and collaboration with influencers, along with regular maintenance across all platforms, forms an effective combination that can strengthen Rinkadaily's brand image and increase its competitiveness in the digital fashion and knitted sweater space. With this approach, Rinkadaily can more effectively reach potential consumers, build positive engagement, and achieve sustainable business growth amidst intense online competition.